KIFC3 Promotes Proliferation, Migration, and Invasion in Colorectal Cancer via PI3K/AKT/mTOR Signaling Pathway - Liao, Huiling; Zhang, Lan; Lu, Shimin; Li, Wei; Dong, Weiguo (Frontiers in Genetics, 2022)
Background: KIFC3, belongs to kinesin superfamily proteins (KIFs), is well known for its role in intracellular cargo movement. KIFC3 has been identified as a docetaxel resistance gene in breast cancer cells, however, the role of KIFC3 and its potential mechanism in colorectal cancer (CRC) remains elusive. Objectives: We aims to investigate the effects of KIFC3 in proliferation, migration, and invasion in CRC as well as the potential mechanism inside. Methods: We investigated the expression of KIFC3 in the Oncomine, Gene Expression Profiling Interactive Analysis databases. The KIFC3 protein expression and mRNA level in CRC cells were evaluated by western blot and qRT-PCR. Cell proliferation ability was detected by CCK-8, EdU, colony formation assay and xenograft tumor in nude mice. Flow cytometry was used to detect the cell cycle. The effect of KIFC3 on the epithelial-to-mesenchymal transition (EMT) was investigated by transwell and wound healing assay. The association of KIFC3 with EMT and PI3K/AKT/mTOR signaling pathway were measured by western blot and immunofluorescence staining. Results: The expression of KIFC3 was higher in CRC tissues than normal colorectal tissue, and was negatively correlated with the overall survival of patients with CRC. KIFC3 silencing inhibited the proliferation, migration and invasion of CRC cells. Meanwhile, it could decrease the number of cells in S phase. KIFC3 silencing inhibited the expression of proliferating cell nuclear antigen, Cyclin A2, Cyclin E1, and CDK2 and increased the expression of p21 and p53. KIFC3 overexpression promoted the G1/S phase transition. KIFC3 silencing inhibited the EMT process, which decreased the level of N-cadherin, Vimentin, SNAIL 1, TWIST, MMP-2, MMP-9 and increased E-cadherin, while KIFC3 overexpression show the opposite results. Furthermore, the knockdown of KIFC3 suppressed the EMT process by modulating the PI3K/AKT/mTOR signaling pathway. KIFC3 silencing decreased the expression of phosphorylated PI3K, AKT, mTOR, but total PI3K, AKT, mTOR have no change. Inversely, the upregulation of KIFC3 increased the expression of phosphorylated PI3K, AKT and mTOR, total PI3K, AKT, mTOR have no change. In a xenograft mouse model, the depletion of KIFC3 suppressed tumor growth. the increased expression levels of KIFC3 could enhance the proliferation, migration and invasion of CRC cells, and enhance the EMT process through the PI3K/AKT/mTOR pathway. Conclusion: Our study substantiates that KIFC3 can participate in the regulation of CRC progression by which regulates EMT via the PI3K/AKT/mTOR axis.